Контроль над вооружениями и военной деятельностью: Справочник - Борисенко А. С. Андрей Станиславович; Лата В. Ф. Василий Филиппович; Маслин Е. П. Евгений Петрович; Орлов В. А. Владимир Андреевич; Сафранчук И. А. Иван Алексеевич; Тимербаев Р. М. Роланд Михайлович; Чуменко Л. Н. Леонид Николаевич (Москва, ПИР-Центр, 2001)
На тит. л. авторы не указ.